(untitled) (PerCursos, 2021)
This paper presents the philosophical practice of Ailton Krenak as the work of a collective subject or a collective person. For such, the Western common sense that consider the philosophical work as an individual task is called into question. Also, notions such as ancestry, memory and tradition will come up in order for us to elucidate Krenak’s proposal of how to deal with the intellectual and cultural repertoire of various philosophical issues in different, new ways. A selection of Krenak’s texts will be analyzed, therefore, to indicate the relations between his ancestral memory and some topics that appear in his philosophical production.